Extraction of chitin from Philippine blue swimming crab (Portunus pelagicus) shells - Fernando, Lorenz Anthony T.; Diaz, Leslie Joy L. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
Chitin, which can be found in the exoskeletons of crustaceans and arthropods, is the second most abundant biopolymer in nature. Among possible sources of chitin are the shells of blue swimming crab (Portunus pelagicus) (BSC), which are considered waste from the food industry. In the Philippines, the BSC captured, for the year 2011, is accounted to be 29,000 MT. Taking this as possible annual production average, the amount of extractable chitin would be around 3,263 - 4,350 MT per year. This amount of chitin can be equivalent to almost Php 3.5 - 200 billion industry ranging from industrial to azure grade of chitin extracted. Chemical extraction of chitin from BSC shells is typically done using a two-stage process: the demineralization (DM) stage and the deproteinization (DP) stage. The DM stage has been shown to be affected by acid concentration, while the DP stage by the BSC shells particle size favoring coarse size particles due to the formation of impervious agglomerates of the finer particle size BSC shells after drying from the DM stage. Further, it has been shown that the rate of DM is governed by diffusion in the product layer which could have been addressed by control on the particle size of the shells. This, however, is inconsistent with the results of the parametric study done because particle size is found to be insignificant. This study, therefore, aims to investigate the reason for such inconsistency with laboratory scale investigations of the stages using Response Surface Box-Behnken design, which can also be used to come up with optimum and/or practical parameters for bench scale extraction. In the DM stage, the three factors considered were acid concentration, BSC shell particle size and reaction time. It was validated that only the acid concentration was found to be a significant factor, in which higher acid concentration tends to increase demineralization of the BSC shells and is consistent with previous study. The design of the experiment conducted allowed us to establish the best possible parameters that can be implemented in the bench scale. Using bench scale set-up, 22,000 ppm Calcium was removed from the shells which corresponds to calcium carbonate removed equals 71% of the initial weight of the BSC shells. The results, however, was not able to resolve the inconsistency with the kinetics study done previously. It is, therefore, suggested that validation of the previous kinetics study be performed. DP investigation was also conducted using Response Surface Box-Behnken design with base concentration, particle size and reaction time as factors considered and with the degree of acetylation (DA) of chitin from the x-ray diffraction (XRD) profiles of the extracted samples as the response variable. The degree of acetylation is indicative of chitin's purity in which higher DA means higher purity of chitin. The factors that significantly affected DA are particle size and interaction between particle size and reaction time. Finer particle sizes are favorable to achieve higher DA of chitin. Small positive effect of longer reaction time as particle size increases can also be observed in the interaction between reaction time and BSC shell particle size. Particle size as a significant factor is supported the kinetics of the DP stage using DA of the extracted sample in which the DP reaction follows product layer diffusion. Best possible parameters obtained from the investigation were validated in the bench scale. The resulting DA of chitin extracted is equivalent to 78.09% with 7.03% difference from that of the expected DA from the laboratory scale, but still higher than the 55% commercially acceptable value of the DA of chitin. Improvements in the methodology were also introduced to enhance mixing of reactants and eliminate unnecessary processes resulting to an increase in chitin yield from 4.8% to 9.6156%. In the end, the amount of resources use to extract chitin were minimized and an increase in the scale of extraction of chitin with high degree of acetylation thus high percent of chitin purity was achieved.
Thesis (M.S. Materials Science and Engineering)--University of the Philippines Diliman
Keywords: Chitin -- Biotechnology; Blue swimming crab -- Philippines; Chitin extraction